PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABLE INTERVENING PADA PT. GARUDAFOOD PUTRA PUTRI JAYA DEPARTMENT HCS (HUMAN CAPITAL AND SERVICE) - HAMDI MEGADINANTA, DIMAS (Jurnal Ilmu Manajemen (JIM), 2017)
In the era of globalization, organizational growth is growing rapidly and competition is increasing. It is proved that the national food and beverage industry is considered strongest in the face of free market competition, especially in the ASEAN Economic Community (MEA). The existence of work motivation that can affect in improving employee performance and through job satisfaction as mediation. The purpose of this study is to test and analyze the effect of work motivation on employee performance through job satisfaction as a variable intervening at PT. Garudafood Putri Jaya Department HCS (Human Capital and Service). The number of samples used is 87 people. The measuring instruments used in this study are interviews, observations, and questionnaires. Data analysis using Partial Least Square (PLS) analysis technique and software Statistical Package for the Social Science (SPSS). The result of the research shows that work motivation has an effect on employee performance, job satisfaction has no effect on employee performance, work motivation influence to job satisfaction, and job satisfaction can mediate the influence of work motivation on employee performance. Keywords: Work Motivation, Employee Performance, Job Satisfaction.